2000
DOI: 10.1177/106286060001500103
|View full text |Cite
|
Sign up to set email alerts
|

Admission Patterns of an Urban Level I Trauma Center

Abstract: Because trauma admission and hospitalization patterns have profound effects on the organization and utilization of urban trauma-care systems, the objective of this study was to identify and analyze these patterns. As an example, admissions to an urban Level I trauma center were reviewed. Retrospective review of all 2029 trauma admissions to a Level I trauma center was conducted from 1993 to 1996. The result was that most trauma patients were young (40% < 30 years of age) and male (74%). Mechanisms of injury we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
15
4

Year Published

2005
2005
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 4 publications
7
15
4
Order By: Relevance
“…The data used by Pape-Köhler et al derived from a different time period from the same register which was used for this study. However, studies from the United States and Norway present similar results with an increased trauma incidence in summer [24,25].…”
Section: Discussionsupporting
confidence: 52%
“…The data used by Pape-Köhler et al derived from a different time period from the same register which was used for this study. However, studies from the United States and Norway present similar results with an increased trauma incidence in summer [24,25].…”
Section: Discussionsupporting
confidence: 52%
“…8 The majority of the international literature, mainly from North America, supports our SGU findings. Ovadia et al 25 and Carmody et al 26 found that more trauma admissions occurred in the evening and overnight than during the day while Laupland et al found that over 70% of major trauma admissions in Canada occurred between 6pm and 8am. 27 Some of the literature is in agreement with our BSUH findings.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have also reported that there is a high incidence of specific mechanisms of injury such as motor vehicle crashes (MVCs), falls, gunshot, stab, assault, and motorcycle crashes (MCCs). 10 11 Similarly, these are the most common mechanisms at our institution. However, there are no studies that have evaluated seasonal variation with specific mechanisms of injury.…”
Section: Introductionmentioning
confidence: 90%